2020
DOI: 10.12933/therya-20-999
|View full text |Cite
|
Sign up to set email alerts
|

A new bat species of the genus Myotis with comments on the phylogenetic placement of M. keaysi and M. pilosatibialis

Abstract: , lophostoma1@gmail (CAC-B). *Corresponding author Molecular studies of Neotropical Myotis (Chiroptera, Vespertilionidae) in the last decade have uncovered substantial cryptic diversity. One example is M. keaysi pilosatibialis, which is characterized by a complex taxonomy derived from low morphological variation. Herein, we studied cryptic diversity of a high elevation clade from premontane and montane forest of Chiriquí Province (Panamá), Cordillera Oriental (Ecuador), and Valle del Silencio (Costa Rica). Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Several samples had been examined in prior studies; for those cases we used the most recently published identification. Vouchers were identified using (Moratelli et al 2013; York et al 2019) as guides, in conjunction with descriptions of new species that have been named more recently (Larsen et al 2012b; Miranda et al 2013; Moratelli et al 2013; Moratelli and Wilson 2014; Moratelli et al 2016 Dec 15; Barquez et al 2017; Moratelli et al 2017; Moratelli et al 2019; Carrión-Bonilla and Cook 2020; Novaes et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several samples had been examined in prior studies; for those cases we used the most recently published identification. Vouchers were identified using (Moratelli et al 2013; York et al 2019) as guides, in conjunction with descriptions of new species that have been named more recently (Larsen et al 2012b; Miranda et al 2013; Moratelli et al 2013; Moratelli and Wilson 2014; Moratelli et al 2016 Dec 15; Barquez et al 2017; Moratelli et al 2017; Moratelli et al 2019; Carrión-Bonilla and Cook 2020; Novaes et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…That study also found that M. nigricans, a species widespread throughout South America, could be as many as twelve distinct cryptic lineages. Since then, from within M. nigricans, nine new species have been recognized (M. dinelli, M. clydejonesi, M. bakeri, M. handleyi, M. attenboroughi, M. izecksohni, M. lavali, M. diminutus, M. larensis, M. midastactus, and M. nyctor) (Larsen et al 2012b;Miranda et al 2013;Moratelli et al 2013; UNRAVELING THE MYOTIS MORASS 5 Moratelli and Wilson 2014;Moratelli et al 2016 Dec 15;Barquez et al 2017;Moratelli et al 2017;Carrión-Bonilla and Cook 2020;Novaes et al 2021).…”
mentioning
confidence: 99%
“…The genus Myotis comprises more than 100 species that originated during the last 10-15 million years [64], representing one of the most successful mammalian radiations. Conflict among morphological classifications, mitochondrial and nuclear gene trees, as well as among individual nuclear loci have been reported [26,65,66], suggesting that the Myotis radiation may have undergone phenomena such as lineage sorting, reticulation, and introgression [65]. Morphological variation is often a poor indicator of species-level relationships among this genus [67]; instead, geography showed to be a better predictor of phylogenetic relationships than morphology [67].…”
Section: Plos Onementioning
confidence: 99%
“…Currently, 28 species of Myotis are recognized from the Neotropics (Moratelli et al 2019a(Moratelli et al , 2019bCarrión-Bonilla and Cook 2020;Novaes et al 2021). However, phylogenetic studies have identified at least 35 independent evolutionary lineages and paraphyletic species, showing that at least 20% of the diversity of neotropical Myotis comprise undescribed species (Clare et al 2007;Larsen et al 2012;Chaverri et al 2016), which is also supported by systematic reviews based on morphological data (e.g., Moratelli et al 2011;Moratelli and Wilson 2014;Novaes et al 2018Novaes et al , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the ruber-group is composed of eight species restricted to the Neotropics: M. ruber (É. Geoffroy, 1806), M. simus Thomas, 1901, M. keaysi J.A. Allen, 1914, M. riparius Handley, 1960, M. elegans Hall, 1962, M. pilosatibialis LaVal, 1973, M. midastactus Moratelli & Wilson 2014, and M. armiensis Carrión-Bonilla & Cook, 2020(Moratelli et al 2013, 2019aCarrión-Bonilla and Cook 2020). However, morphological and molecular evidence indicate that the species diversity in the ruber-group may be underestimated (Clare et al 2011;Moratelli and Wilson 2014;Novaes et al 2017;Carrión-Bonilla and Cook 2020).…”
Section: Introductionmentioning
confidence: 99%